UMBILICAL HERNIA IN CALVES: INCIDENCE AND TREATMENT - ALASAD, R. N. I; GHAZI, A. J. (The Iraqi Journal of Veterinary Medicine, 1996)
Six thousandand thirty three calves have been examined for umbilical hernia within the years 1990 to 1995 in 3 different veternary clinics and 688 (11.4%) were suffering from umbilical hernia. All affected calves were treated surgically with complete recovery within two weeks, except for few that have shown other secondary complication